Students’ Perception on English Teachers’ Teaching style at SMAN 1 Kota Gorontalo: A Qualitative Study - Lidya Putri Anggraini Mohammad; Kartin Lihawa; Syahrun Ibrahim (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to explore and describe students’ perceptions of English teachers’ teaching styles at SMA Negeri 1 Kota Gorontalo. It employed a qualitative approach with a case study design. The participants consisted of 21 eleventh-grade students and two English teachers. Data were collected through semi-structured interviews and classroom observations, and analyzed using thematic analysis to identify key patterns and themes. The findings reveal that students generally have positive perceptions of their teachers’ teaching styles. The teachers predominantly applied democratic and expressive styles, characterized by a relaxed and comfortable classroom atmosphere, two-way communication, the integration of learning technologies such as videos and presentations, and the use of relevant examples and storytelling. These approaches were found to enhance students’ motivation, participation, and confidence in speaking English. However, some students still experienced difficulties in grammar and pronunciation and showed diverse learning preferences. In conclusion, teaching styles play a crucial role in shaping students’ perceptions and fostering an effective and engaging English learning environment. Therefore, teachers are encouraged to develop interactive, varied, and student-centered teaching strategies to accommodate diverse student needs.